Effects of Different Doses of Plant Growth Regulators on Some Characteristics of Summer Snowflakes (Leucojum aestivum L.) - Mehmet Uğur Yıldırım; İbrahim Bulduk; Ercüment Osman Sarıhan; Gözde Küçük; Sinem Tuğçe Cin; Ahmet İzmirli (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine the effect of different doses and combinations of benzylaminopurine (BAP) and Putrescine elicitor on some plant characteristics of summer snowflake (Leucojum aestivum L.). The experiment was conducted for two years between 2017-2019 in the greenhouse of Uşak University, Faculty of Agriculture and Natural Sciences. Bulbs with ~7 cm circumference and ~9 g weight were used as a material of this study, and was constructed with randomized blocks design with 3 replications. The bulbs were treated for 24 hours before planting with 5, 10 and 15 mg/l BAP; 5, 10 and 15 mg/l Putrescine elicitor in different combinations (16 different combinations). Thereafter, all bulbs were planted in crates. In the first year, only plant height, number of leaves per bulb were recorded and at the end of the second year, the plant height, number of leaves per bulb, number of leaves per daughter bulb, number of bulbs, leaf weight, root length and weight, bulb weight, unit bulb weight, alkaloid contents were measured after removal of bulbs from the soil. According to the results, plant height ranged 19,3-30,0 cm; the number of leaves ranged 6.5 to 12.6, and the number of bulbs ranged 0.9 to 4.6. Root weight was determined between 13.4-47.1 g/parcel, fresh leaf weight ranged 12.4-49.2 g/parcel, and one bulb weight was between 3.5-14.6 g. It was determined that the bulb plant was influenced by different treatments. The maximum growth was noted with 5 mg/l Putrescine elicitor treatment that increased plant height, number of leaves per bulb each year and number of bulbs.